Cloud-Computing: A milestone in Information Technology (International Journal of Engineering and Computer Science, 2018)
-In the recent booming era, the information technology is developed which offers human entertainment, convenience, enjoyment etc. Cloud computing is one of emerging development of IT industry. It is one of the IT services which based on leased and provide service to customer over a network. It also known as on-demand computing. The services of cloud-computing are managed by third party. It provides scalability, reliability, high performance and low cost as compared to dedicated infrastructure and saves managing cost and time. Most of sectors like Banking, public healthcare, and education are approaching towards the cloud due to efficient utilization of cloud services on pay-per-use basis. Cloud computing is completely an internet dependent technology where client data is stored and maintain in the data centre of cloud provider like Google, Amazon, Microsoft etc. The aim of this paper is better understanding about cloud computing and their design. This research paper outlines about cloud and all the details.